Some Features of Composite Formation and Classification of Composites in Russian Language - Madaminova Nargiza Rajapbayevna (Researchparks Publishing, 2022)
This article touches upon the problems of Russian word formation. The issues related to one of the productive ways of word formation - word composition (compositing) are revealed. The definitions of the definitions of a compound word and a composite from different sources and from different authors are given. The classification of composites is described in detail.